Diagnostic, prognostic and therapeutic considerations in primary pulmonary hypertension - Chapman, P J (Division of Pulmonology, 2017)
The diagnosis of primary pulmonary hypertension (PPH) and prediction of its course, whether treated or untreated, presents several problems. These are of particular relevance when selection of patients for, and timing of heart-lung transplantation is being considered. I performed a retrospective study on patients with PPH and chronic large vessel thromboembolic pulmonary hypertension (TPH) seen at Groote Schuur Hospital between 1957 and 1985 in an attempt to: 1. Establish the diagnostic and prognostic value of clinical features, lung function tests, cardiac catheterisation, isotope lung scans and, in the PPH group, response to therapy; 2. Review our experience of the effects of treatment with vasodilators and oral anticoagulants, and the results of heart and lung transplantation in the PPH group; 3. Attempt to identify features which could be used to predict prognosis in PPH; and thereby 4. Define criteria for selecting PPH patients whose prognosis could be improved by heart-lung transplantation.